Sulforaphane attenuates glycoprotein VI-mediated platelet mitochondrial dysfunction through up-regulating the cAMP/PKA signaling pathway in vitro and in vivo. Issue 8 (22nd March 2023) - Zhou, Xinyu; Huang, Xinhui; Wu, Chunting; Ma, Yongjie; Li, Weiqi; Hu, Jinqiu; Li, Rong; Ya, Fuli
Abstract : Treatment of SFN in human platelets or 12-week supplementation of SFN-enriched BSE in mice attenuates GPVI-mediated mitochondrial dysfunction, apoptosis and activation, which depends on decreasing PDE3A activity and up-regulation of the cAMP/PKA pathway. Abstract : Platelet mitochondrial dysfunction is crucial for platelet activation, atherosclerosis and thrombosis. Sulforaphane (SFN) is a dietary isothiocyanate enriched in cruciferous vegetables and possesses multiple health benefits including cardiovascular protection. This study aims to investigate whether and how SFN modulates platelet mitochondrial dysfunction and hyperactivity in vitro and in vivo . Using a series of platelet functional assays in human platelets in vitro, we found that SFN at physiological concentrations attenuated oxidative stress-dependent platelet mitochondrial dysfunction (loss of mitochondrial membrane potential), apoptosis (cytochrome c release, caspase 3 activation and phosphatidylserine exposure) and activation induced by glycoprotein VI (GPVI) agonists ( e.g., collagen and convulxin). Moreover, 12-week supplementation of SFN-enriched broccoli sprout extract (BSE, 0.06% diet) in C57BL/6J mice also attenuated GPVI-induced platelet mitochondrial dysfunction, apoptosis and hyperreactivity in vivo . Mechanistically, these inhibitory effects of SFN treatment and BSE supplementation were mainly mediated by up-regulating the cAMP/PKA pathway though decreasing phosphodiesterase 3A (PDE3A) activity. Thus, through modulating the PDE3A/cAMP/PKA signaling pathway, and attenuating platelet mitochondrial dysfunction and hyperreactivity, SFN may be a potent cardioprotective agent.